O-GlcNAcylation of NONO regulates paraspeckle component assembly and contributes to colon cancer cell proliferation - Yeolhoe Kim; Kyung-Tae Lee; Han Byeol Kim; Hyeryeon Jung; Jeong Yeon Ko; Tae Hyun Kweon; Hari Chandana Yadavalli; Junghwa Seo; Suena Ji; Yun Ju Kim; Donghyuk Shin; Seong Wook Yang; et al. (Cell Death Discovery)
Abstract Non-POU domain-containing octamer-binding protein (NONO) is a multifunctional member of the Drosophila behavior/human splicing (DBHS) protein family with DNA- and RNA-binding activity. NONO is highly expressed in various types of cancer, and excessive O-GlcNAcylation has also been implicated in tumorigenesis. Although recent studies revealed that NONO is O-GlcNAcylated and that this modification is involved in DNA damage repair, it remains unknown whether O-GlcNAcylation of NONO regulates cancer cell proliferation. Additionally, little is known about the effect of O-GlcNAcylation on other biological properties of NONO. In this study, we identify Thr440 as the primary NONO O-GlcNAcylation site and demonstrates its crucial role in the assembly of paraspeckles, an important subnuclear compartment that facilitates NONO-dependent transcriptional regulation in mammalian cells. Moreover, we found that O-GlcNAcylation of NONO is required to maintain the expression of genes related to microtubule cytoskeleton organization involved in mitosis and to suppress the expression of genes related to cellular response to type I interferon. Regarding the regulation of these genes, depletion of NONO O-GlcNAcylation at Thr440 significantly inhibited the proliferation of colon cancer cells. Collectively, our findings highlight NONO O-GlcNAcylation as a key regulator modulating paraspeckle formation and as a candidate therapeutic target in colon cancer.